Diffusion and reactivity in ultraviscous aerosol and the correlation with particle viscosity. Issue 2 (20th November 2015) - Marshall, Frances H.; Miles, Rachael E. H.; Song, Young-Chul; Ohm, Peter B.; Power, Rory M.; Reid, Jonathan P.; Dutcher, Cari S.
Abstract : Direct comparison of diffusion coefficients and viscosities of ternary component single aerosol particles levitated using optical tweezers. Abstract : The slow transport of water, organic species and oxidants in viscous aerosol can lead to aerosol existing in transient states that are not solely governed by thermodynamic principles but by the kinetics of gas-particle partitioning. The relationship between molecular diffusion constants and particle viscosity (for example, as reflected in the Stokes–Einstein equation) is frequently considered to provide an approximate guide to relate the kinetics of aerosol transformation with a material property of the aerosol. We report direct studies of both molecular diffusion and viscosity in the aerosol phase for the ternary system water/maleic acid/sucrose, considering the relationship between the hygroscopic response associated with the change in water partitioning, the volatilisation of maleic acid, the ozonolysis kinetics of maleic acid and the particle viscosity. Although water clearly acts as a plasticiser, the addition of minor fractions of other organic moieties can similarly lead to significant changes in the viscosity from that expected for the dominant component forming the organic matrix (sucrose). Here we highlight that the Stokes–Einstein relationship between the diffusion constant of water and the viscosity of the particle may be more than an order of magnitude in error, even at viscosities as low as 1 Pa s. We show that the thermodynamic relationships of hygroscopic response that underpin such kinetic determinations must be accurately known to retrieve accurate values for diffusion constants; such data are often not available. Further, we show that scaling of the diffusion constants of organic molecules of similar size to those forming the matrix with particle viscosity may be well represented by the Stokes–Einstein equation, suppressing the apparent volatility of semi-volatile components. Finally, the variation in uptake coefficients and diffusion constants for oxidants and small weakly interacting molecules may be much less dependent on viscosity than the diffusion constants of more strongly interacting molecules such as water.